The Role of Intellectual Security in Protecting Society from Extremism According to Islamic Legislation - صالح حيزومه شاكر رشيد; صالح عمار باسم (Tasnim International Journal for Human, Social and Legal Sciences, 2024)
The research tried to highlight that the concept of intellectual security is one of the modern concepts that were not known in our Islamic culture in its wording, but its content is ancient, as Islamic intellectual security is a necessary need, life is not straight without it; Rather, it is the basis of security for societies in general, and it is the most important of them, and the basis for their existence and continuity, as it is an essential element in preserving the five necessities that the Islamic Sharia came to preserve. The research showed that what helps religious coexistence in multi-sectarian and multi-religious countries is the expansion of the circle of belonging in the country, and that acquaintance, rapprochement and achieving peace is one of the goals for which man was created. The research showed that the Islamic intellectual security is a prominent feature of the establishment of the Islamic society in the era of the Prophet, and it is one of the foundations of the protection of society from temptations, and its slipping into the corridors of darkness. General and in the city document in particular. The research highlighted a number of facts after the introductions leading to it were addressed. The research showed the importance of activating the right of citizenship in society and the effective mechanism to reduce strife and sectarian, ethnic and sexual conflicts in any society on the basis of equality and non-discrimination. Rejecting extremism has an impact on the consolidation of an important goal of the purposes of Sharia, which is to preserve people’s minds, from declining towards corrupt perceptions and deviant ideas. Therefore, it has become necessary to warn the common people against entering into understanding scientific issues and building their perceptions according to their own readings that are not disciplined by the principles and rules of thinking. Scientific and academic. The research confirmed that the Qur’anic text showed, through its connotations, the importance of the element of citizenship in the life of a Muslim. Therefore, we find that it presented to us a number of experiences that the prophets of God went through while they were subjected to a state of forced evacuation from their country. The research concluded that peaceful coexistence is an agreement, acceptance and moral reconciliation between people in their dealings and transactions wherever they are at the same time and place.